2012
DOI: 10.1016/j.jacc.2011.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Noninvasive Myocardial Perfusion Imaging Using Single-Photon Emission Computed Tomography, Cardiac Magnetic Resonance, and Positron Emission Tomography Imaging for the Detection of Obstructive Coronary Artery Disease

Abstract: SPECT, CMR, and PET all yielded a high sensitivity, while a broad range of specificity was observed. SPECT is widely available and most extensively validated; PET achieved the highest diagnostic performance; CMR may provide an alternative without ionizing radiation and a similar diagnostic accuracy as PET. We suggest that referring physicians consider these findings in the context of local expertise and infrastructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
230
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(239 citation statements)
references
References 37 publications
(31 reference statements)
4
230
4
1
Order By: Relevance
“…Despite challenges, false‐negative MR perfusion studies are uncommon. A recent meta‐analysis of perfusion MR revealed false‐negative rates of 0–16% from the 34 vasodilator stress studies analyzed, comparable to our incidence of 5% of all CE‐MARC patients 6. The largest study in the meta‐analysis (21 false‐negative patients) was prone to verification bias, as it was neither randomized nor prospective 17.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Despite challenges, false‐negative MR perfusion studies are uncommon. A recent meta‐analysis of perfusion MR revealed false‐negative rates of 0–16% from the 34 vasodilator stress studies analyzed, comparable to our incidence of 5% of all CE‐MARC patients 6. The largest study in the meta‐analysis (21 false‐negative patients) was prone to verification bias, as it was neither randomized nor prospective 17.…”
Section: Discussionsupporting
confidence: 76%
“…While having a significant univariate relationship to a false‐negative finding, this was not the case when adjusting for other variables. In the meta‐analysis described above,6 there was no significant chronological change in false‐negative rates, suggesting that improvements in imaging technique, while striving to improve diagnostic accuracy, may have a limited role in reducing the frequency of false‐negative results. Consistent with this notion, we found that most false‐negative results were associated with factors outside of the imaging acquisition.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…82 Rb MPS has been validated for the diagnosis of obstructive CAD and is as sensitive but more specific than SPECT MPS. 13,14 Accordingly, 82 Rb offers the only current realistic choice of tracer if widespread adoption of PET MPS was to be recommended.…”
Section: Which Pet Tracer Is a Realistic Choice For Widespread Use Inmentioning
confidence: 99%
“…[16][17][18][19]30,31 Adenosine stress perfusion CMR is highly sensitive, specific, and reproducible for identification of obstructive CAD and has been reported to be superior to other stress imaging methods for this purpose. [32][33][34][35][36][37][38] In the setting of stable, nonobstructive CAD, patients with proven microvascular disease based on invasive coronary reactivity testing had lower MPRI as compared with healthy controls. 39 In our study, when stress perfusion was abnormal in patients with LGE or T2+, abnormal perfusion was typically identified in the affected myocardial segments.…”
Section: Cmr Evidence Of Infarction (Lge)mentioning
confidence: 99%